Screening of flavonoid aglycons’ metabolism mediated by the human liver cytochromes P450 - Benković Goran; Bojić Mirza; Maleš Željan; Tomić Siniša (Acta Pharmaceutica)
Biological effects of flavonoids have been extensively studied in the last 80 years. As flavonoids represent a rather large group of compounds, data on metabolic biotransformations of these compounds is relatively limited to those well studied. The objective of this study was to screen the metabolism of 30 selected flavonoid aglycons mediated by the most relevant metabolic enzymes, human liver cytochromes P450. For this purpose, in vitro experiments with human liver microsomes and recombinant enzymes were conducted. To evaluate flavonoid’s metabolism and structure of the products, high-performance liquid chromatography coupled with high-resolution mass spectrometry was used. Out of 30 flavonoids, 15 were susceptible to oxidative metabolism mediated by cytochromes P450. Dominant reactions were aromatic hydroxylation and O-demethylation, or a combination of these reactions. The dominant enzyme responsible for the observed metabolic reactions is CYP1A2, whereas other human liver cytochromes P450, namely, CYP2C19, CYP2D6, CYP2E1 and CYP3A4, contribute to flavonoid metabolism to a lesser degree. These results, to some extent, contribute to the understanding of the metabolism of constituents found in antioxidant dietary supplements and their possible interactions with other xenobiotics, i.e., medicinal products.